Thrombolysis Combined Therapy Using CuS@SiO2-PEG/uPA Nanoparticles - Fu, Dapeng; Fang, Qingbo; Yuan, Fukang; Liu, Junle; Ding, Heyi; Chen, Xuan; Cui, Chaoyi; Ding, Jinhui (Frontiers in Chemistry, 2021)
Massive hemorrhage caused by the uncontrolled release of thrombolysis drugs is a key issue of thrombolysis therapy in clinical. In this study, we report a NIR light triggered drug delivery system, i.e. CuS@mSiO2-PEG (CSP) nanoparticles, for the loading of a thrombolytic drug (urokinase plasminogen activators, uPA). CSP nanoparticles with the CuS nanoparticles as photothermal agents and the mesoporous SiO2 for the loading of uPA were synthesized using a facile hydrothermal method. The CSP core-shell nanoparticles were demonstrated to possess excellent photothermal performance, exhibiting a photothermal conversion efficiency up to 52.8%. Due to the mesoporous SiO2 coating, the CSP core-shell nanoparticles exhibited appropriate pore size, high pore volume and large surface area, thus they showed great potential to be used as drug carriers. Importantly, the release of uPA from CuS@mSiO2-PEG/uPA (CSPA) carriers can be promoted by the near-infrared (NIR) laser irradiation. The drug loading content of uPA for the as-prepared NIR-triggered drug delivery system was calculated to be 8.2%, and the loading efficiency can be determined to be as high as 89.6%. Due to the excellent photothermal effect, the NIR-triggered drug delivery system can be used for the infrared thermal imaging in vivo due to the photothermal effect of CSP nanocarriers. The in vivo thrombolysis assessment demonstrated that the NIR-triggered drug delivery system showed excellent thrombolytic ability under the irradiation of an 808 nm laser, showing the combined therapy for thrombolysis. As far as we know, the CSPA core-shell nanoparticles used as NIR-triggered drug delivery system for thrombolysis have not been reported.